HERBAL SUPPLEMENT INNOVATION BASED ON LOCAL WISDOM - Aditya Candra; Tahara Dilla Santi; Ika Waraztuty; Said Aandy Saida; Andri (RADJA PUBLIKA, 2026)
The use of herbal plants as local wisdom in the Gampong Nusa community urgently requires innovation in the development of safe and effective muscle relaxant supplements. The purpose of this study was to provide education and training on innovative ways to make herbal medicines based on Moringa leaves, which can improve community knowledge and skills. A participatory approach was used, involving 16 participants. The empowerment results showed an 85% increase in knowledge and skills in formulating muscle relaxant supplements from Moringa leaves. It is hoped that this innovative education and training can support the development of safe and sustainable herbal medicines based on local wisdom at the village level, as well as improve community health.